Conformational Response of Influenza A M2 Transmembrane Domain to Amantadine Drug Binding at Low pH (pH 5.5) - Georgieva, Elka R.; Borbat, Peter P.; Grushin, Kirill; Stoilova-McPhie, Svetla; Kulkarni, Nichita J.; Liang, Zhichun; Freed, Jack H. (Frontiers in Physiology, 2016)
The M2 protein from influenza A plays important roles in its viral cycle. It contains a single transmembrane helix, which oligomerizes into a homotetrameric proton channel that conducts in the low-pH environment of the host-cell endosome and Golgi apparatus, leading to virion uncoating at an early stage of infection. We studied conformational rearrangements that occur in the M2 core transmembrane domain residing on the lipid bilayer, flanked by juxtamembrane residues (M2TMD21-49 fragment), upon its interaction with amantadine drug at pH 5.5 when M2 is conductive. We also tested the role of specific mutation and lipid chain length. Electron spin resonance (ESR) spectroscopy and electron microscopy were applied to M2TMD21-49, labeled at the residue L46C with either nitroxide spin-label or Nanogold® reagent, respectively. Electron microscopy confirmed that M2TMD21-49 reconstituted into DOPC/POPS at 1:10,000 peptide-to-lipid molar ratio (P/L) either with or without amantadine, is an admixture of monomers, dimers, and tetramers, confirming our model based on a dimer intermediate in the assembly of M2TMD21-49. As reported by double electron-electron resonance (DEER), in DOPC/POPS membranes amantadine shifts oligomer equilibrium to favor tetramers, as evidenced by an increase in DEER modulation depth for P/L’s ranging from 1:18,000 to 1:160. Furthermore, amantadine binding shortens the inter-spin distances (for nitroxide labels) by 5-8 Å, indicating drug induced channel closure on the C-terminal side. No such effect was observed for the thinner membrane of DLPC/DLPS, emphasizing the role of bilayer thickness. The analysis of continuous wave (cw) ESR spectra of spin-labeled L46C residue provides additional support to a more compact helix bundle in amantadine-bound M2TMD21-49 through increased motional ordering. In contrast to wild-type M2TMD21-49, the amantadine-bound form does not exhibit noticeable conformational changes in the case of G34A mutation found in certain drug-resistant influenza strains. Thus, the inhibited M2TMD21-49 channel is a stable tetramer with a closed C-terminal exit pore. This work is aimed at contributing to the development of structure-based anti-influenza pharmaceuticals.